Side Effect of Antigipsy Stigma. Ponticelli's Case and the Prejudice in Public and Legal Speech - Cappanera, Carla (Mediterranean Journal of Social Sciences, 2012)
In this paper I would like to show, through a case-study analysis, how political, legal, media topics about Roma people, in Italy,are shaped by some negative believes and stereotypes. This frame lead to creating, in the common sense, the idea of danger that gobeyond real situation.The stereotype that I want to analyze – that is part of the elements that led to sentence for three Roma women overlast thirty years – is constituted by association of ideas between Roma woman and children’s kidnapper.